Exercer o cuidado : narrativas no contexto de residência médica em hospital - Giaretta, Davisson Gonçalves (2018)
Professional practice in healthcare undoubtedly involves caring for the other. For an effective humanized care, the condition of mutuality is emphasized, from which it also integrates the subjectivity of the professional. This Masters Dissertation aimed to apprehend and to understand in depth the professional and formative experience of resident physicians in a scenario marked by tensions between the working and learning conditions offered and the respondent to the subject for an effective practice of care in the urgency and emergency hospital context. In order to comply with this proposition, two Sections composes this study, one theoretical and the other, empirical. The first section, entitled Between the care and chaos: reflections about the doctor practice in urgency and emergency hospital context, contemplated a reflection on medical practice in urgency and emergency hospital context, marked by the poor working conditions and the specific characteristics like unpredictability and readiness to act. The ethics of care in Psychoanalysis and Humanization in Health proposed by the National Humanization Politics are guidilines to this discussion. Narrative vignettes of four resident physicians were used as an illustrative resource for this problematization.In the Empirical Section, called Care urgencies and emergencies: resident physicians’ narratives,the aim was to explore the narratives of eight resident physicians whose professional practice occurs in the urgency and emergency hospital context during the Residence. Data from the interviews were analyzed through Interpretative Analysis. Therefore we have found that the Medical Residence is sought as a specialization of excellence in Medicine. However, the doctor, when becomes a resident, is faced with demands and requirements that take on excess, which inevitably brings effects, often harmful, to his subjectivity and to his professional identity formation process. Finally, since the implication of the physician's subjectivity in his work is evident, it is necessary to pay attention to the professional’s condition of affectation, thus avoiding indifference practices both towards the other and to himself. That is, the effective practice of mutuality in care becomes an essential factor of protection and promotion of psychic health of these professionals. It is concluded,therefore, that institutional attention is essential in the direction to offer genuine and official spaces that promote reflection and criticism on what is effectively experienced by resident doctors, from the recognition and reception of their unique demands.